1998
DOI: 10.1508/cytologia.63.305
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Mixoploidy in Maize Anthers.

Abstract: Summary Cytogenetic analysis on two lots of maize genotypes consisting of inbred lines, singlecross hybrids and double-cross hybrids grown in the South and Center West Regions of Brazil revealed the occurrence of spontaneous mixoploidy in the anthers of some plants. In the South Region the anthers showed only diploid and tetraploid cells, with the tetraploid ones presenting nuclear fusion. In the genotypes grown in the Center West Region the anthers showed a mixture of diploid, tetraploid, hexaploid and octapl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…For example, in one anther we may find different anomalies, characterized as typical meiotic mutations, which do not affect all cells. Similar variation in expression of some meiotic mutations among genotypes originated from CNPMS populations have already been described (see Taschetto and Pagliarini, 1993;Defani-Scoarize et al, 1995aCaetano-Pereira et al, 1995a, 1998a, 1998b, 1999Pagliarini, 1996, 1997).…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…For example, in one anther we may find different anomalies, characterized as typical meiotic mutations, which do not affect all cells. Similar variation in expression of some meiotic mutations among genotypes originated from CNPMS populations have already been described (see Taschetto and Pagliarini, 1993;Defani-Scoarize et al, 1995aCaetano-Pereira et al, 1995a, 1998a, 1998b, 1999Pagliarini, 1996, 1997).…”
Section: Resultssupporting
confidence: 67%
“…All genotypes originally came from populations of the National Center of Research on Maize and Sorghum (CNPMS/Embrapa). Analyses with genotypes provided by Organization of Cooperatives of the State of Paraná (Taschetto and Pagliarini, 1993;Defani-Scoarize et al, 1995a and genotypes provided by PLANAGRI S.A., a private breeding enterprise (Caetano-Pereira et al, 1995a1998a, 1998b, 1999Pagliarini, 1996, 1997), showed high meiotic instability. Although the two cultivation sites, i.e., Cascavel in the south-western region of Paraná, Brazil, and Goianésia in the center-western state of Goiás, Brazil, are separated by more than 1500 km, the distinct genotypes analyzed had similar meiotic abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…This assumption is due to the fact that inbred lines from distinct locations, but of common origin, were much more affected than heterozygous genotypes, and the phenotypic expression of this abnormality was much higher when the lines were cultivated on acid soils. Mixoploidy also occurred in this group of genotypes (Caetano-Pereira et al, 1998a), and 13 genotypes out of 43 evaluated presented pollen mother cells with different levels of ploidy in the same anther, ranging from diploidy to octaploidy. In plants cultivated in southern Brazil all cells with altered ploidy levels presented nuclear fusion, i.e., all chromosomes shared the same nucleus, but in plants cultivated in the center western region, in addition to this type of behavior for 4n cells, other cells (4n, 6n and 8n) only showed cytoplasm fusion, with the nuclei remaining individualized.…”
Section: Resultsmentioning
confidence: 71%
“…It is observed in extreme conditions such as near borders of or on physiological limits of the species existence with some potential adaptive advantage for them [17]. The causative phenomenon of mixoploidy were cytomixis, syncytia, defective cytokinesis and spindle irregularities in the premeiotic mitoses [6]. The species under study showed hypolploid and hyperploid cells.…”
Section: Discussionmentioning
confidence: 99%
“…In such cases, mixoploidy is a potential force in evolution [18]. This cytogenetic phenomenon will reduce fertility, produce unbalanced gametes, suppress meiosis and eventually decrease the productivity of plants [6]. A high level of mixoploidy may be a sign of a high degree of genome plasticity which serves to increase the adaptivity of the plant [14].…”
Section: Discussionmentioning
confidence: 99%